Pengaruh Kualitas Produk, Promosi Dan Citra Merek Terhadap Kepuasan Pelanggan di Outlet Hokben Ciracas - Purnomosidi, Irvan; Raja Unggul Saragih, Darwin (Rifa'Institute, 2023)
This study aims to analyze the influence of product quality, promotion, and brand image on customer satisfaction at Hokben Ciracas outlets. This study used a Likert scale with 100 respondents to measure relation among variables. The data were collected and processed with SPSS v.26 software and analyzed. The analysis result showed that product quality has a positive and significant effect on customer satisfaction, promotion has a positive and significant impact on customer satisfaction, and brand image has a positive and significant influence on customer satisfaction. In addition, it was also found that the three variables, namely product quality, promotion, and brand image, simultaneous have a positive effect on customer satisfaction. And these results can be the basis for improving marketing strategies and customer service quality in the restaurant industry in the future.